Digitalização de documentos: implicações no acesso às informações arquivísticas - Schäfer, Murilo Billig (2013)
The digitization of archival documents has become a common activity in Federal Institutions of Higher Education (IFES) in Brazil, justified by the need for flexible access to archival information, elements that serve as an aid in the performance of administrative activities and for making decision. Moreover, when it comes to historical collections and culturally relevant, scanning enables researchers and stakeholders access to information which reconstruct the trajectory of a given organization or local, affecting the diffusion of documentary heritage. Given this, studies are needed to define parameters that enable the digital capture achieving the objectives for which the digital surrogate were created, in the specific case of this research, the purpose of access to information. Thus, the aim of this study was to investigate and recommend specifications (resolution, file formats, color depth) focused on the process of scanning documents from the Universidade Federal da Fronteira Sul (UFFS) seeking access to archival information. The specific objectives guided into: point out the implications of digitization for access to archival information that constitutes its documentary heritage; present the legal aspects that involve scanning documents in the Brazilian context, identify archival documents scanned by examining the use of representatives digital result of this process, as well as find out if there are tools (manuals, guides, recommendations, etc..) that provide guidance on the process of scanning, analyzing the specifications adopted in scanning according to the purpose of access to information, and make recommendations focused on the process of scanning documents with the purpose of access to information. Given the above objectives, we performed the analysis of the context of document scanning in UFFS, evaluating the specifications adopted in accordance with the purpose of access to information. It was concluded that digital capture adopted in the institution facilitates access to information, but it presents the possibility of adjustments that would result in better management of digital surrogate over time. Thus Recommendations were prepared for Scanning Documents: Purpose Access to archival information, which contains guidelines aimed at digital capture of documents UFFS. Although these recommendations are directed to the context of the institution, can serve as a reference for other digitization projects that have implications for the access and preservation of archival information.